Measuring Entrepreneurial Intentions of Students in Northwestern Croatia - Ivana Bujan Katanec; Barbara Pisker; Danijela Magdalenić (Social Sciences, 2024)
This study explores the factors influencing entrepreneurial intentions among students in northwestern Croatia, with a focus on educational background, family entrepreneurial environment, studying experiences, and perceived self-efficacy. Empirical research was conducted between March and June 2024 on a sample of 160 students from northwestern Croatia, and a multiple regression analysis was performed to identify key predictors of entrepreneurial intentions. The results revealed that entrepreneurial self-efficacy significantly impacted students’ intentions to start and run successful businesses, aligning with prior research on entrepreneurial behavior. However, other factors, such as family background and entrepreneurial education, showed no significant influence in this specific regional context. The findings suggest that educational programs should emphasize developing entrepreneurial self-efficacy to foster future entrepreneurs. This study highlights the importance of integrating entrepreneurial activities, such as business plan competitions and start-up incubators, into the curriculum. Limitations related to sample size and cross-sectional design are acknowledged, and future research is encouraged to explore additional factors and larger samples. This research provides valuable insights for educators and policymakers seeking to enhance students’ entrepreneurial capacities and support regional economic development.